XML and Perl - Riehl, Mark; Sterin, Ilya (Sams, 2002)
If you are a Perl programmer looking to explore Perl's XML capabilities or an XML developer with a basic understanding of Perl, this book will provide you with all the tools required for XML processing with Perl. XML and Perl teaches you to create portable, powerful, and extensible applications when you use XML and Perl together. You'll also learn to customize your XML processing facilities to accomplish unique tasks. Authors Mark Riehl and Ilya Sterin, who have written Perl XML modules and administer the official Perl XML web site (www.perlxml.net), have filled this book with practical code samples and exercises that will help you test drive your new knowledge. With this book, you'll quickly see the advantages of using XML and Perl together, and you'll be able to perform even complicated tasks more easily with powerful Perl XML modules.